Addressing the tissue specificity of U5 snRNP spliceosomopathies - Kemal, Rahmat Azhari; O’Keefe, Raymond T. (Frontiers in Cell and Developmental Biology, 2025)
Precursor mRNA (pre-mRNA) must undergo splicing to remove intron sequences and join exons. This splicing process is catalysed by an RNA/protein complex called the spliceosome. At the centre of the catalytic spliceosome is the U5 small nuclear ribonucleoprotein (snRNP). Pathogenic variants in U5 snRNP core proteins are associated with various diseases commonly known as spliceosomopathies. Variants in TXNL4A and EFTUD2 manifest in craniofacial malformations while variants in PRPF8 and SNRNP200 manifest in retinitis pigmentosa. This perspective highlights research addressing how these specific manifestations come about as the spliceosome is required in all cells and at all developmental stages. Cell and animal models can replicate the human clinical specificity providing explanations for the specificity of the disorders. We propose that future research could benefit from models originating from patient-derived induced pluripotent stem cells (iPSCs) and isogenic controls to compare the coding and non-coding transcriptomic perturbations. Analysis of spliceosomal protein complexes and their interactome could also uncover novel insights on molecular pathogenesis. Finally, as studies highlight changes in metabolic processes, metabolomic studies could become a new venture in studying the consequences of U5 snRNP variants.